(untitled) (Research, Society and Development, 2025)
Climate change is a global challenge that requires academic training focused on sustainability and affirmative climate action. The objective of this article is to determine the level of knowledge in environmental education about affirmative climate actions among business administration students at ESPAM – MFL. To address this need, a descriptive, non-experimental study with a mixed approach was conducted among business administration students in their first to third semesters using a purposive sample. Structured surveys were administered before and after an educational intervention based on the Farmer Field Schools (FFS) methodology, adapted to higher education, which integrated participatory activities, digital materials, and interactive talks. The results show a significant increase in knowledge and appreciation of affirmative climate actions, with 80% acceptance among women in the early semesters and a willingness to change habits in 75% of participants post-intervention. However, neutral positions persist among male and advanced-level students, representing up to 40% in certain cases. In conclusion, the educational strategy was effective in strengthening environmental commitment; however, it is necessary to implement differentiated approaches that address sociodemographic variations in order to consolidate a sustainable culture in administrative training.